Current Treatment of Toxoplasma Retinochoroiditis: An Evidence-Based Review - Meredith Harrell; Petros E. Carvounis (Journal of Ophthalmology)
Objective. To perform an evidence-based review of treatments for Toxoplasma retinochoroiditis (TRC). Methods. A systematic literature search was performed using the PubMed database and the key phrase “ocular toxoplasmosis treatment” and the filter for “controlled clinical trial” and “randomized clinical trial” as well as OVID medline (1946 to May week 2 2014) using the keyword ‘‘ocular toxoplasmosis’’. The included studies were used to evaluate the various treatment modalities of TRC. Results. The electronic search yielded a total of 974 publications of which 44 reported on the treatment of ocular toxoplasmosis. There were 9 randomized controlled studies and an additional 3 comparative studies on the treatment of acute TRC with systemic or intravitreous antibiotics or on reducing the recurrences of TRC. Endpoints of studies included visual acuity improvement, inflammatory response, lesion size changes, recurrences of lesions, and adverse effects of medications. Conclusions. There was conflicting evidence as to the effectiveness of systemic antibiotics for TRC. There is no evidence to support that one antibiotic regimen is superior to another so choice needs to be informed by the safety profile. Intravitreous clindamycin with dexamethasone seems to be as effective as systemic treatments. There is currently level I evidence that intermittent trimethoprim-sulfamethoxazole prevents recurrence of the disease.